2015
DOI: 10.4244/eijy14m08_06
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-man clinical evaluation of Ultimaster, a new drug-eluting coronary stent system: CENTURY study

Abstract: The Ultimaster™ novel bioresorbable polymer sirolimus-eluting stent demonstrated good performance, including high procedural success and strong suppression of neointimal proliferation at six months. Good safety and effectiveness were shown up to two years in the studied population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 25 publications
3
27
0
Order By: Relevance
“…18 Hence, newer DES were developed with biodegradable polymers and thinner struts to improve the clinical outcomes, even in complex lesions. [19][20][21] The clinical outcomes of the ISAR-3 trial also favour biodegradable polymer-coated DES rather than permanent polymer-coated DES. 22 Recently, pooled analysis of large multicentre randomised trials also showed a lower risk of TVR and very late ST associated with biodegradable polymers compared with durable polymer-coated DES.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Hence, newer DES were developed with biodegradable polymers and thinner struts to improve the clinical outcomes, even in complex lesions. [19][20][21] The clinical outcomes of the ISAR-3 trial also favour biodegradable polymer-coated DES rather than permanent polymer-coated DES. 22 Recently, pooled analysis of large multicentre randomised trials also showed a lower risk of TVR and very late ST associated with biodegradable polymers compared with durable polymer-coated DES.…”
Section: Discussionmentioning
confidence: 99%
“…The CENTURY study, a first-in-man experience of the Ultimaster coronary stent (Terumo Corp, Tokyo, Japan), is a thin-strut, Co-Cr, bioresorbable polymer-coated SES, which reported 1.0% (1 incidence in 105 patients) clinically driven TLR in patients with de novo lesions (in up to two native coronary arteries). 20 In the EVOLVE trial, the incidence of TLR was found to be 1.1% in 94 patients treated with the Synergy stent for de novo artherosclerotic lesions. 26 However, longer follow-up of patients receiving the Supraflex SES will be necessary to confirm long-term safety of this DES and this is being undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…The newly developed Ultimaster DES (BP‐SES, Terumo Corporation, Tokyo, Japan) incorporates several innovative features, such as bioresorbable polymer (resorbed within 3–4 months) and abluminal gradient coating, features that are expected to translate into positive clinical outcome . In the CENTURY II, a large (N = 1,123), randomized, multicentre trial, BP‐SES were compared with everolimus‐eluting, permanent polymer Xience stents (PP‐EES).…”
Section: Introductionmentioning
confidence: 99%
“…The newly developed Ultimaster DES (BP-SES, Terumo Corporation, Tokyo, Japan) incorporates several innovative features, such as bioresorbable polymer (resorbed within 3-4 months) and abluminal gradient coating, features that are expected to translate into positive clinical outcome. 12 In the CENTURY II, a large (N ¼ 1,123), randomized, multicentre trial, BP-SES were compared with everolimus-eluting, permanent polymer Xience stents (PP-EES). The results of the study revealed that BP-SES was noninferior to PP-EES in the incidence of target lesions failure after 9 months, the composite of cardiac death, myocardial infarction or clinically driven target lesion revascularization (TLR)-the primary endpoint of the study.…”
Section: Introductionmentioning
confidence: 99%
“…The primary endpoint of the CENTURY I study, angiographic late loss at 6 months, was 0.04±0.35 mm and was significantly lower than late loss in the control arm (Table 4) [65]. Through 4 years of follow-up, the rate of TLF was 6.7% and ARC definite/probable ST was 0.9% [66].…”
Section: Clinical Trials Of Bioabsorbable Polymer-coated Desmentioning
confidence: 99%